COMPARATIVE ANALYSIS THE RESULTS OF RADIOLOGICAL EXAMINATION OF PATIENTS WITH EARLY RHEUMATOID ARTHRITIS - Вершиніна, Д. В.; Рижик, В. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The article presents the results of a comparison of the complex radiological examination of patients with early rheumatoid arthritis, which included an conventional X-ray, wrist MRI and two-photon X-ray densitometry of the radius. The correlations between clinical variants of rheumatoid arthritis and a frequency detecting MR symptom sand change sin bone mineral density were established. The advantages of MRI in the diagnosis of wrist lesion sin early rheumatoid arthritis were demonstrated.